PENGARUH VIDEO BASED LEARNING, KEMUDAHAN PENGGUNAAN, DAN MANFAAT, TERHADAP KEPUASAN PENGGUNA YANG DIMEDIASI OLEH KESENANGAN PADA KONSUMEN KURSUS ONLINE RUBRIK GRAFIS - Wahyu Abdillah; Ilsya Hayadi (UNIB Press, 2025)
The purpose of this study was to examine the effect of video based learning, ease of use, and usefulness on user satisfaction mediated by enjoyment on online courses Rubrik Grafis. The sampling technique in this study used an simple random sampling technique, which was measured using the Hair sampling technique, which was 5 to 10 times the number of indicators. The data collection technique uses a questionnaire that is distributed online via the Telegram group. Measurement research in this questionnaire consists of 24 questions to respondents. The number of samples is 163, which are users of the Rubrik Grafis online course from all over Indonesia. The analytical tool used PLS-SEM with the assistance program SmartPls version 3.2.9. the result showed that (1) video based learning has a positive effect on enjoyment; (2) ease of use has a positive effect on enjoyment; (3) usefulness has a positive effect on enjoyment; (4) video based learning has a positive effect on user satisfaction (5) ease of use has a positive effect on user satisfaction (6) usefulness has a positive effect on user satisfaction (7) enjoyment has a positive effect on user satisfaction; (8) enjoyment mediates the effect video based learning on user satisfaction; (9) enjoyment mediates the effect ease of use on user satisfaction; (10) enjoyment mediates the effect usefulness on user satisfaction. This research has an impact on online course developers to pay attention to various factors so that users feel satisfied.